1994
DOI: 10.1103/physrevb.50.8402
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and initial growth phase of diamond thin films on (100) silicon

Abstract: The nucleation of diamond on silicon (100) in a methane-in-hydrogen microwave plasma has been investigated by atomic force microscopy (AFM), scanning electron microscopy (SEM), and reflection high energy electron diffraction (RHEED). The nucleation of diamond was performed by application of an electrical substrate potential. It was found that three-dimensional non-facetted islands are initially formed whose sizes increase with the deposition time. In spite of their very small sizes of a few nanometers, RHEED r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(73 citation statements)
references
References 30 publications
3
63
0
Order By: Relevance
“…[12][13][14] Beckmann et al 15 noted that this change in the plasma chemistry was too small to account for the nucleation enhancement. Jiang, Schiftman, and Klages 16 found that the overall temporal evolution of nucleation density agreed well with a surface kinetic model proposed by Tomellini, Polini, and Sessa. 17 They further suggested that ion bombardment plays a decisive role in the BEN process.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…[12][13][14] Beckmann et al 15 noted that this change in the plasma chemistry was too small to account for the nucleation enhancement. Jiang, Schiftman, and Klages 16 found that the overall temporal evolution of nucleation density agreed well with a surface kinetic model proposed by Tomellini, Polini, and Sessa. 17 They further suggested that ion bombardment plays a decisive role in the BEN process.…”
Section: Introductionsupporting
confidence: 64%
“…9. At an ion dose of 10 16 cm Ϫ2 , only two peaks at about 820 and 980 cm Ϫ1 for SiC and Si can be observed. As the ion dose increased to 10 17 cm…”
Section: ϫ2mentioning
confidence: 99%
“…[11][12][13] On the other hand, for silicon, an enhanced surface mobility of active species during BEN leads to a depletion zone around each diamond nucleus. 14 In the later case, the measured distributions were shifted to larger distances compared to the random case. In the present study, the Poisson analysis of the nearest-neighbor distribution clearly showed that surface diffusion of carbon species on the Ir ͑100͒ surface is not the driving force for nucleation during the HFCVD-BEN step.…”
Section: Discussionmentioning
confidence: 96%
“…This behavior is quite different from the one reported for BEN-MWCVD process on iridium [11][12][13] and silicon. 14 On iridium, diamond-oriented particles are agglomerated forming domains. [11][12][13] On the other hand, for silicon, an enhanced surface mobility of active species during BEN leads to a depletion zone around each diamond nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…This will be kept layer-by-layer growth due to adatom diffusion. Jiang et al [14] indicated that the first-nearest-neighbor distance among the nuclei was about 10 nm determined by experiments. Thus, Ascarelli et al [15] concluded that the maximum nucleation density was limited at 10 12 cm ± ±2…”
Section: Effect Of Nucleation Rate On Heteroepitaxial Diamond Growth mentioning
confidence: 98%